Alteration of N6-Methyladenosine mRNA Methylation in a Human Stem Cell-Derived Cardiomyocyte Model of Tyrosine Kinase Inhibitor-Induced Cardiotoxicity - Ma, Yan; Liu, Xian; Bi, Yiming; Wang, Tianhu; Chen, Cheng; Wang, Yabin; Han, Dong; Cao, Feng (Frontiers in Cardiovascular Medicine, 2022)
Background N6-methyladenosine (m6A) plays important roles in various cardiovascular diseases (CVDs), including cardiac hypertrophy and heart failure. Sunitinib (SUN) is a tyrosine kinase inhibitor (TKI) that is widely used in the treatment of different types of solid and blood tumors, but its efficacy is restricted by a concomitant rise in cardiotoxicities. However, the methylation modification of m6A messenger RNA (mRNA) in cardiomyocytes treated with TKI has not been investigated. Methods The global m6A methylation level of SUN-induced cardiotoxicity was detected by m6A dot blot and colorimetric methylation assay. MeRIP-Seq (methylated RNA immunoprecipitation sequencing) and RNA-seq (RNA sequencing, input) were employed to depict the landscapes of transcriptome and epitranscriptome in TKI. Changes in major m6A-related enzymes were detected by qRT-PCR and Western blot. In addition, the effects of FTO on SUN-induced cardiotoxicity were evaluated by gain and loss of function studies. Results In this study, we observed that the m6A methylation level was significantly elevated in SUN-treated human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) and paralleled a positively correlated cellular damage level. Through a genome-wide analysis of m6A mRNA methylation by methylated RNA immunoprecipitation sequencing (MeRIP-seq) and input RNA sequencing (RNA-seq), we identified a total of 2,614 peaks with significant changes, of which 1,695 peaks were significantly upregulated and 919 peaks were significantly downregulated. Quantitative reverse transcription PCR (RT-qPCR), immunofluorescence, and Western blotting revealed that the RNA demethylase fat mass and obesity-associated protein (FTO) was downregulated, whereas the RNA methylases methyltransferase-like 14 (METTL14) and wilms' tumor 1-associating protein (WTAP) were upregulated. Furthermore, gain- and loss-of-function studies substantiated that FTO is cardioprotective in TKI. Conclusion This study deciphered the methylation modification of m6A mRNA in hiPSC-CMs post-TKI treatment and determined that FTO may be a promising therapeutic target for TKI-induced cardiotoxicity.